Profile of Children Admitted with Respiratory Syncytial Virus Infections in a Quaternary Care Hospital in Kerala, India - Irshad M; Jeeson Unni (Pediatric Infectious Disease)
Aims and background: Respiratory infections are fairly common in pediatric age group, and respiratory syncytial virus (RSV) is a frequently encountered etiological agent. It is known to occur as seasonal outbreaks. This study was conducted to know the profile of the kids admitted with RSV during a probable outbreak in Kerala, India. Materials and methods: This was a retrospective descriptive study of data from the electronic medical record (EMR) of children admitted from September 1 to October 31, 2023 to one of four pediatric units of our hospital when the institute had a peak in the number of admissions for respiratory illnesses. Data of all children who had been tested with QIAstat respiratory panel and were positive for RSV were analyzed for their clinical presentation, laboratory investigations, and treatment. Results: An etiological agent was identified in 32 out of 35 cases for whom the viral respiratory panel was tested (91%). RSV was detected in 23 cases. It was more common among infants. Approximately 79% of them had fever, and 21% had respiratory distress. Thrombocytosis and elevated C-reactive protein (CRP) were seen in 21% and 52% of cases, respectively. Around 17% required oxygen via nasal prongs, and 9% required high-flow nasal cannula (HFNC). Only one case with septicemia was treated with antibiotics. All children with RSV infection had an uneventful recovery. Conclusions: Identification of viral agent during outbreaks of respiratory infections would reduce the unnecessary use of antibiotics and oseltamivir.